2005
DOI: 10.1093/toxsci/kfj030
|View full text |Cite
|
Sign up to set email alerts
|

DNA Hypermethylation of Promoter of Gene p53 and p16 in Arsenic-Exposed People with and without Malignancy

Abstract: Chronic arsenic exposure is known to produce arsenicosis and cancer. To ascertain whether perturbation of methylation plays a role in such carcinogenesis, the degree of methylation of p53 and p16 gene in DNA obtained from blood samples of people chronically exposed to arsenic and skin cancer subjects was studied. Methylation-specific restriction endonuclease digestion followed by polymerase chain reaction (PCR) of gene p53 and bisulfite treatment followed by methylation-sensitive PCR of gene p16 have been carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
152
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(161 citation statements)
references
References 22 publications
6
152
1
2
Order By: Relevance
“…Some reports demonstrated that arsenic could induce p53 accumulation in an ATM-dependent pathway (44); the overexpressed p53 was a mutant form, and most frequent mutation sites were found in exons 5 and 8, so mutated p53 subsequently led to its normal function loss. Other studies (45)(46)(47) documented that the promoter of p53 in arsenic-exposed cells exhibited hypermethylation as some carcinoma appeared; consequently, p53 expression decreased, resulting in its function loss or partial loss, so the cells were predisposed to uncontrolled proliferation, genomic instability, or apoptosis. In our study, p53 did not show mutations in its coding region upon chronic arsenic treatment, yet its protein expression was remarkably decreased relative to the control cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports demonstrated that arsenic could induce p53 accumulation in an ATM-dependent pathway (44); the overexpressed p53 was a mutant form, and most frequent mutation sites were found in exons 5 and 8, so mutated p53 subsequently led to its normal function loss. Other studies (45)(46)(47) documented that the promoter of p53 in arsenic-exposed cells exhibited hypermethylation as some carcinoma appeared; consequently, p53 expression decreased, resulting in its function loss or partial loss, so the cells were predisposed to uncontrolled proliferation, genomic instability, or apoptosis. In our study, p53 did not show mutations in its coding region upon chronic arsenic treatment, yet its protein expression was remarkably decreased relative to the control cells.…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic has been associated with gene-specific hypermethylation of p53 and p16 promoter regions in blood DNA of subjects exposed to toxic level of arsenic compared to controls. 60 Hypermethylation of the p16 promoter was also observed in WBC DNA from 103 patients with arseniasis compared to 110 healthy subjects. 61 Air pollution.…”
mentioning
confidence: 96%
“…And the data of low-dose TCS exposure on ESR1 gene methylation levels suggests that the p16 gene hypermethylation may be the gene-special change in TCS exposed HepG2 cell. Actually, some environmental chemicals can induce p16 gene hypermethylation, such as particulate matter 2.5 (Soberanes et al, 2012), arsenic (Chanda et al, 2006;Zhang et al, 2007), nickel (Govindarajan et al, 2002), HCB, TCDD (Ozden et al, 2015), and chromium (Kondo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%